Focusing a Gender Lens on Emergency Medicine Research: 2012 Update. (20th March 2013) - McGregor, Alyson J.; Greenberg, Marna; Safdar, Basmah; Seigel, Todd; Hendrickson, Robert; Poznanski, Stacey; Davenport, Moira; Miner, James; Choo, Esther K.; Gerson, Lowell W.
Abstract The influence of sex and gender on patient care is just being recognized in emergency medicine (EM). Providers are realizing the need to improve outcomes for both men and women by incorporating sex‐ and gender‐specific science into clinical practice, while EM researchers are now beginning to study novel sex‐ and gender‐specific perspectives in the areas of acute care research. This article serves as an update on the sex differences in a variety of acute clinical care topics within the field of EM and showcases opportunities for improving patient care outcomes and expanding research to advance the science of gender‐specific emergency care.